Management of Guillain-Barre Syndrome with SARS-CoV-2 Infection in Pediatrics: A Case Series - Arora, Jatin; Manjunath, Kavya (Indian Journal of Pharmacy Practice)
Guillain-Barre Syndrome (GBS) is an immune-mediated response that causes muscle and limb weakness. Coronavirus 2019 (COVID-19) is an infectious disease caused by the attack of Severe Acute Respiratory Syndrome Coronavirus 2 viruses (SARS-CoV-2) in which patients show symptoms such as fever, cough, and headache. We had studied five different cases of pediatric patients who came across GBS secondary to COVID-19. The analyzed cases represent patients between 2-16 years old who were admitted with complaints of muscle weakness, back pain, difficulty walking, and ascending paralysis with clinical findings of SARS-CoV-2 infection. Each patient’s diagnosis was confirmed by a number of factors like Cerebrospinal fluid (CSF) analysis, nerve study and Magnetic Resonance Imaging (MRI) scan, and Intravenous Immunoglobulin (IVIG) therapy was given to stop the disease progression. The analysis shows that it is very crucial to carry out tests for COVID-19 before confirmation of the diagnosis because there are high chances of GBS even in case of sub-clinical COVID-19.
Keywords: SARS-CoV-2; Guillain-Barre syndrome; IVIG